74‐1: A New Flexible Thin Film Encapsulation Structure with High Reliability and Wide Color‐Viewing‐Angle. Issue 1 (29th May 2019) - Guo, Tianfu; Wang, Kan; Lu, Rui; Fan, Congcong; Wang, Yijia; Huang, Jing; Hsu, Hsiang Lun
Abstract : We report a new thin film encapsulation structure composited of atomic layer deposition layer and organic wrinkles, which show a 13% improvement in color‐viewing‐angle with no decrease in storage lifetime. We also made a demo with the new TFE film, and shows an excellent flexibility performance, which indicates a great potential in wide viewing‐angle flexible display applications.